Disrupted development and integrity of frontal white matter in patients treated for pediatric medulloblastoma - Glass, John O (Neuro Oncol, 2017)
BACKGROUND: Treatment of pediatric medulloblastoma is associated with known neurocognitive deficits that we hypothesize are caused by microstructural damage to frontal white matter (WM). METHODS: Longitudinal MRI examinations were collected from baseline (after surgery but before therapy) to 36 months in 146 patients and at 3 time points in 72 controls. Regional analyses of frontal WM volume and diffusion tensor imaging metrics were performed and verified with tract-based spatial statistics. Age-adjusted, linear mixed-effects models were used to compare patient and control images and to associate imaging changes with Woodcock–Johnson Tests of Cognitive Abilities. RESULTS: At baseline, WM volumes in patients were similar to those in controls; fractional anisotropy (FA) was lower bilaterally (P < 0.001) and was associated with decreased Processing Speed (P = 0.014) and Broad Attention (P = 0.025) performance at 36 months. During follow-up, WM volumes increased in controls but decreased in patients (P < 0.001) bilaterally. Smaller WM volumes in patients at 36 months were associated with concurrent decreased Working Memory (P = 0.026) performance. CONCLUSIONS: Lower FA in patients with pediatric medulloblastoma compared with age-similar controls indicated that patients suffer substantial acute microstructural damage to supratentorial frontal WM following surgery but before radiation therapy or chemotherapy. Additionally, this damage to the frontal WM was associated with decreased cognitive performance in executive function 36 months later. This early damage also likely contributed to posttherapeutic failure of age-appropriate WM development and to the known association between decreased WM volumes and decreased cognitive performance.